STRATEGY FOR SELECTING CANDIDATE WELLS FOR HYDRAULIC FRACTURING IN FIELD X TO MAXIMIZE THE PRODUCTION POTENTIAL OF MATURE FIELDS - Ludianti, Fida
Along with the difficulties in finding new fields and the technical challenges in their development, the role of mature fields is becoming increasingly important in the oil and gas industry. In such situations, effective and long-lasting recovery of mature field assets becomes crucial for production operations. Hydraulic fracturing is one of the stimulation techniques used to enhance production rates. However, the implementation of hydraulic fracturing requires significant costs, necessitating a strategy for selecting candidate wells for hydraulic fracturing to maximize the production potential of mature fields. A case study was conducted in Field X, which has a sandstone lithology and is an oil reservoir with a range of medium to high permeability. In selecting wells suitable for stimulation, the Heterogeneity Index (HI) map and Estimated Ultimate Recovery (EUR) calculations were used, employing the Reciprocal and Decline Curve Analysis methods. Out of the 24 wells in Field X, three candidate wells were selected for hydraulic fracturing: TM-6, TM-14, and TM-19. The appropriate model chosen for the selected wells was the KGD 2D model, resulting in optimal fracture designs for the candidate wells, with fracture half-length (????????) values of 346 ft, 268 ft, and 263 ft for TM-6, TM-14, and TM-19, respectively. Using the optimal fracture designs, the post-hydraulic fracturing flow rates were determined for TM-6, TM-14, and TM-19, which were 873 BFPD, 1599 BFPD, and 1154 BFPD, respectively. The analysis of the Inflow Performance Relationship, using the Sukarno (1986) and Wiggins (1994) methods in this field, indicated that hydraulic fracturing can enhance well performance, as evidenced by the increasing Absolute Open Flow (AOF) values. The workflow for selecting candidate wells in this study is expected to serve as a guide in determining suitable wells for hydraulic fracturing.